2015
DOI: 10.5380/abclima.v17i0.41493
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Climáticos Do Estado De Minas Gerais (Climate Aspects in Minas Gerais State)

Abstract: RESUMO:A caracterização do clima de um determinado local é um aspecto importante para vários setores da economia como, por exemplo, na prática agrícola. Diante disso, o objetivo desse estudo é apresentar alguns dos principais aspectos climáticos do estado de Minas Gerais (MG): precipitação, temperaturas mínima, média e máxima, intensidade e direção dos ventos a 10 metros de altura, classificação climática de Köppen-Geiger e índice de aridez. Para isso, se utilizaram dados de diferentes fontes. Entre os resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 12 publications
3
13
1
14
Order By: Relevance
“…Nonetheless, in the present study, atypical air temperatures were observed in the period of higher development for the two species, which corresponds to Sd11 and Sd12 (from March to September 2016), with T med values from 17.2 to 18.1ºC. These values are inferior to the climatic mean values of the studied region, which range from 20.1 to 21ºC (Reboita et al, 2015). This may have contributed to the lower-estimated optimum temperature values for both species.…”
Section: Resultscontrasting
confidence: 71%
“…Nonetheless, in the present study, atypical air temperatures were observed in the period of higher development for the two species, which corresponds to Sd11 and Sd12 (from March to September 2016), with T med values from 17.2 to 18.1ºC. These values are inferior to the climatic mean values of the studied region, which range from 20.1 to 21ºC (Reboita et al, 2015). This may have contributed to the lower-estimated optimum temperature values for both species.…”
Section: Resultscontrasting
confidence: 71%
“…The soil of the experimental area has a clayey texture, and the climate of the region is classified as humid subtropical (Cwa), with a rainy season in the summer and a drought season in the winter [19]. Meteorological data (precipitation and temperature) during the experiment are presented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The pilot study was conducted with three male greater rheas held by Belo Horizonte Zoo, Brazil (S 19°51' , W 44°01'): hereafter BH Zoo. The mean annual temperature varies between 18°C and 24°C, and the annual pluviometric mean of 1,460 mm, with two distinct seasons: a dry season from April to September and a rainy season from October to March, being the climate classified as Aw in the Köeppen system (Reboita et al, 2015). Birds were exposed to visitors six days a week (Tuesday to Sunday).…”
Section: Study Area Housing and Maintenancementioning
confidence: 99%